Colocolic Intussusception: A Case Report of an Uncommon Manifestation of Peutz-Jeghers Syndrome - Alyhari, Qasem; Al-Wageeh, Saleh; Ahmed, Faisal; Mohammed, Hanan; Dahan, Noha; Alhadi, Asad (AL-Kindy College Medical Journal, 2025)
Peutz-Jeghers syndrome is a rare genetic disorder resulting from defects in signaling pathway regulation, marked by gastrointestinal hamartomas and mucocutaneous pigmentation. This condition can lead to complications such as intussusception, with colocolic intussusception being particularly rare. We present the case of a 30-year-old female who exhibited acute on chronic abdominal pain and progressive distension, along with digital and perioral hyperpigmentation. Unfortunately, her diagnosis of Peutz-Jeghers syndrome was delayed until she developed intestinal obstruction. Imaging revealed large bowel obstruction with proximal bowel dilatation, prompting a left hemicolectomy and end-to-end colocolic anastomosis. The patient experienced an uneventful postoperative recovery and remained symptom-free during follow-up. This case highlights the rarity of colocolic intussusception as a manifestation of Peutz-Jeghers syndrome and emphasizes the importance of early recognition and intervention to prevent bowel obstruction and the need for extensive surgical procedures.